Analisis Kondisi Sanitasi Lingkungan Penderita Ascariasis dan Trichuriasis Anak Sekolah Dasar Di Kota Yogyakarta (Studi Kasus) - Siti Hani Istiqomah; Soebijanto Soebijanto; Agus Suwarni (Poltekkes Kemenkes Yogyakarta, 2011)
Indonesia is a tropical country where parasites can grow well and causing in-fection among people due to poor environmental sanitation, lack of individual hygiene and low social economic condition. Diseases caused by Ascaris lumbricoides and Trichuris trichiura are public health problems in Indonesia, of which 60 – 80% of their prevalence occurs among school children. According to the result of faeces examination conducted by the Health Office of Yogyakarta Municipality and Indonesian Family Planning Asociation of Yog-yakarta, there are 197 children suffering from Ascariasis and Trichuriasis. The objective of the study was to analyze the environmental sanitation condition of children’ houses and schools. The research was a case study consisted of qualitative and quantitative data collection. Research instruments used were checklist for the observation of environmental sanitation and indepth interview guidance to obtain qualitative data. Independent sample t-test at 95% significance level showed results that the p-values for environmental sanitation condition of houses was 0.817 and of schools was 0.144. The result of Pearson correlation test for environmental sanitation condition yielded p-values 0,045 for houses and 0,022 for schools. There was correlation between environmental sanitation condition of home and of school in among Ascariasis and Trichuriasis. The results of descriptive analysis showed that there were 15 houses (39%) of 38 Ascariasis sufferers which had poor home sanitation condition; out of the 126 Trichuriasis sufferers there were 64 houses (51%) which had adequate home sanitation condition and 42 houses (33%) which had poor home sanitation condition. Among the condition of school envi-ronment sanitation of Ascariasis sufferers, 18 children (47%) were from ade-quate category and among the condition of school environment sanitation of Trichuriasis sufferers, 52 children (41%) belong to poor category. Qualitatively, children's individual hygiene practices were low, such as had dirty short/long nails, often playing outdoor, had direct contact with soil and excreted at rivers.